ANALISA KEKERASAN MATERIAL HASIL ANNEALING PADA PIPA LONG ELBOW MATERIAL STAINLESS STEEL ASTM 304 L MENGGUNAKAN HARDNESS TESTER - Muhdori; Abdillah, Hamid; Raka Irawan (Politeknik Negeri Cilacap, 2023)
Bending is a process of mixing materials which results in convexity while other parts become concave due to the influence of force or bending moment. During the bending process, it results in different pipe strains, which cause permanent strains. The annealing process (heat treatment) is a process for changing the metal structure by heating the specimen. The aim of this research is to analyze the material hardness of the ASTM 304 L stainless steel long elbow pipe after the annealing process is carried out, the test is carried out at various angles, namely (0°, 90°, 180°, and 270°) using the Hardness Tester. The method used in this research is an experimental method, a research procedure carried out to determine the effects of the annealing treatment given to the material. The research results from the 0° angle have a material hardness of 156 HB, from the 90° angle the material hardness is 140 HB, from the 1800 angle the material hardness is 164 HB, from the 2700 angle the material hardness is 159 HB, the conclusion is that the annealing process and the inner angle of the long elbow pipe has a significant influence on the hardness of stainless steel materials. Keywords: elbow pipe, annealing, hardness tester.